Pengaruh Word of Mouth dan Social Media Activities Terhadap Minat Beli Konsumen Menantea Jawa Barat - Annisa Aulia; Felicia Abednego (Jurnal Bisnis dan Manajemen (JBM), 2023)
Abstract Modernization era has changed many aspects including business aspect, especially in food and beverages industry. Competition is also increasing along with the emergence of brands or food and beverage products in Indonesia. So it takes the ability to survive and compete in the market, one of which is by maintaining buying interest from consumers. This research was conducted with the aim of examining the influence of Word of Mouth and Social Media Activities on the Buying Interests of Menantea Consumers in West Java. This research is a quantitative research with data collection techniques through questionnaires. The specified population is all people in the area of West Java. By using a sampling technique, namely purposive sampling, the sample in the study was 180 people with various different backgrounds. In the research process, the analysis was carried out using the Multiple Linear Regression Analysis technique with the help of SPSS software. Based on the analysis that has been done, the results show that Word of Mouth and Social Media Activities individually or partially affect consumer buying interest. Key words: Word of Mouth, Social Media Activities, Purchase Intention.